2000
DOI: 10.1103/physrevd.61.071701
|View full text |Cite
|
Sign up to set email alerts
|

CPviolation in hyperon decays from supersymmetry

Abstract: It was pointed out recently that supersymmetry can generate flavor-changing gluonic dipole operators with sufficiently large coefficients to dominate the observed value of ⑀Ј/⑀. We point out that the same operators contribute to direct CP violation in hyperon decay and can generate a CP violating asymmetry A(⌳ Ϫ 0 ) in the range probed by the current E871 experiment. Interestingly, models that naturally reproduce the relation ϭͱm d /m s do not generate ⑀Ј/⑀ but could lead to an A(⌳ Ϫ 0 ) of O(10 Ϫ3 ).The origi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 32 publications
2
52
1
Order By: Relevance
“…It is found that the result is consistent with that given in Ref. [1], and A(Λ 0 − ) could be range of O(10 −3 ).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…It is found that the result is consistent with that given in Ref. [1], and A(Λ 0 − ) could be range of O(10 −3 ).…”
supporting
confidence: 91%
“…[1] that B p and B s quantify the uncertainty in the matrix elements analysis, we can therefore expect that A(Λ 0 − ) could also be O(10 −3 ) in the present letter. In conclusion, we have restudied the supersymmetric contribution to the CP -violating asymmetry in hyperon non-leptonic decay Λ → pπ.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…A Λ is estimated to be (2 − 5) × 10 −5 in the standard model [9,11], but it can be as large as a few times 10 −4 in the other models [12][13][14]. For the charged Ξ → Λπ decay, A Ξ is expected to be smaller than A Λ by about a factor of ten because the strong phase shifts of the Λπ final state are predicted to be small [15].…”
mentioning
confidence: 99%
“…The baryon asymmetry of the universe can in principle be understood in terms of CP violation [6], but the CKM contribution to CPV is too small by many orders of magnitude [7], suggesting that additional contributions from new physics were at play in the early universe. Proposed Standard Model extensions (e.g., non-minimal SUSY [8], multi-Higgs models [9], left-right-symmetric models [10,11], and the SME of Kostelecký et al [12]) abound in possible new, CP-violating phases, which could account for the baryon asymmetry and could show up in sensitive heavy-quark experiments. These issues have motivated substantial, world-wide efforts seeking to discover physics beyond the Standard Model in neutral-meson mixing and CPV.…”
Section: Tapas Physics Overviewmentioning
confidence: 99%